The Impact of Islamic Work Ethics and Motivation on Employee Performance: A Case Study of BMT Ar-Rahmah Jaya Mulia, Central Lampung - Peftiani, Widia; Ekawati, Evi; Ramdani, Rahmat Fajar (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
This research aims to determine the influence of Islamic work ethics and work motivation on employee performance, in this study quantitative methods. The population used is all employees at BMT Ar-Rahmah Jaya Mulia Central Lampung, totalling 35 employees. The sampling technique used is a saturated sampling technique, where the entire population is sampled in the study so that a research sample of 35 employees is obtained. At the same time, the data collection technique used is the distribution of questionnaires. Data is processed using SmartPLS version 4.0. The results show that Islamic work ethics have a positive and significant effect on employee performance, and work motivation has a positive and significant effect on employee performance.